Spermatozoa Membrane Permeability in Sterlet (Acipenser ruthenus L) and Carp (Cyprinus carpio L) - Puhovkin, Anton Yu.; Butskyi, Kyrylo I. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):178.